Targeted Proteomic Analysis of Glycolysis in Cancer Cells - Murphy, J. Patrick; Pinto, Devanand M (Journal of proteome research, 2011)
Altered expression of glycolysis proteins is an important yet poorly understood characteristic of cancer. To better understand the glycolytic changes during tumorigenesis, we designed a liquid chromatography multiple reaction monitoring (LC−MRM) assay targeting the “glycolysis proteome” in MCF-7 breast cancer cells, using isotope-coded dimethylation of peptides for relative quantification. In silico, dimethyl labeled tryptic peptides [M + 2H]2+ (of length n) and their y n-1 fragment ions were determined based on UniprotKB database sequence entries for glycolysis proteins, related branching pathways, and reference proteins. Using predicted transitions ([M + 2H]2+ → y n-1), MRM-initiated detection and sequencing (MIDAS) was performed on a dimethyl-labeled, tryptic digest from MCF-7 cells, using two-dimensional liquid chromatography mass spectrometry analysis. Three transitions for each peptide were selected from identified spectra and assessed using 1D-LC−MRM-MS. Collision energy (CE) and dwell times were optimized and matching transitions for “heavy” isotope-coded dimethylated peptides were calculated. Resulting LC−MRM transitions were then used to measure changes in the glycolytic proteome in insulin-like growth factor-1 (IGF-1)-stimulated MCF-7 cells and other breast cell lines. Increases in the expression of glycolysis proteins leading to lactic acid production were observed common to IGF-1-stimulated MCF-7 cells and the invasive MDA-MB-231 cell line. Preliminary analysis of lung tumors with varied states of differentiation demonstrated the clinical applicability of LC−MRM and showed decreased levels of PGK1 in poorly differentiated tumors.